The Institution of waqf as an Instrument of peace and security in Nigeria (2013)
This paper addresses the challenge of insecurity which is engendered in Nigeria by gross economic inequality and extreme poverty. As a lasting solution, the paper therefore suggests the redistribution of wealth through the instrumentality of the Islamic institution of waqf (charity endowment). The institution of waqf would reduce the impact of economic shocks, provide social wages and generate employment for the poor. It would also assist the target group by providing sustainable welfare packages to them. Without doubt, the full utilisation of the institution of waqf would reinforce the pillars of love and brotherhood, and stimulate enduring peace and security in the country.